Triglyceride-to-High-Density Lipoprotein Cholesterol Ratios in Prediabetics With a Normal Range of Low-Density Lipoprotein Cholesterol - Afaq, Madeeha; Haider, S. Sabahat; Mir, Myra (Biological and Clinical Sciences Research Journal, 2025)
The triglyceride-to-high-density lipoprotein cholesterol ratio is an emerging marker of insulin resistance and metabolic syndrome. It may identify cardiovascular risk even in individuals with normal low-density lipoprotein cholesterol levels. Early detection is particularly important in Pakistan, where the burden of prediabetes is rapidly increasing. Objective: To determine the frequency of prediabetes across triglyceride to high-density lipoprotein cholesterol ratio quintiles among adults with normal low-density lipoprotein cholesterol levels. Methods: This descriptive cross-sectional study was conducted at the Department of Chemical Pathology, Sheikh Zayed Hospital, Rahim Yar Khan, from January to July 2024. A total of 131 adults aged 25 to 65 years with low-density lipoprotein cholesterol levels between 50 and 100 mg/dL were enrolled using non-probability, consecutive sampling. Prediabetes was defined as fasting blood glucose levels of 100 to 125 mg/dL or glycated hemoglobin levels of 5.7 to 6.4 percent. Participants were categorized into five quintiles based on the triglyceride-to-high-density lipoprotein cholesterol ratio. Demographic, clinical, and biochemical variables were recorded and analyzed using SPSS version 20. Associations were assessed using chi-square tests, with p-values of 0.05 or less considered statistically significant. Results: The mean age of participants was 44.6 ± 10.1 years, and 54.2 percent were female. The overall frequency of prediabetes was 29.0 percent. A progressive increase in prediabetes prevalence was observed across triglyceride-to-high-density lipoprotein cholesterol ratio quintiles, rising from 4.3 percent in the lowest quintile to 48.1 percent in the highest quintile, indicating a statistically significant association (χ² = 22.76, p < 0.001). No significant differences were found with respect to gender, educational status, or place of residence. Conclusion: The triglyceride-to-high-density lipoprotein cholesterol ratio is significantly associated with prediabetes among individuals with normal low-density lipoprotein cholesterol levels. Its simplicity and low cost support its potential use as a practical screening tool for early identification of metabolic risk in the Pakistani population.